1987
DOI: 10.1007/bf01402292
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic stress in lateral saccular aneurysms

Abstract: The flow velocities in lateral glass and silastic aneurysm models were quantitatively measured with the non-invasive laser Doppler method. The influences of the elasticity of the wall, the pulse wave and the properties of the perfusion medium on the intra-aneurysmal circulation were investigated. As shown previously, the inflow into the aneurysm arose from the downstream lip and was directed toward the centre of the fundus. Backflow to the parent vessel took place along the walls of the fundus. With non-pulsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…On the other hand, all values of g have the highest t w =ðrU 2 max Þ occurring around the distal orifice lip. This observation is similar to that of Steiger et al (1987) and of Lo¨w et al (1993) in their rigid or elastic lateral aneurysm models of g ¼ 0 . Suzuki and Ohara (1978) in their in vivo investigation pointed out that the blood flow often leads to the orifice wall reinforced by proliferation of intima.…”
Section: Wall Shear Stress and Pressuresupporting
confidence: 88%
“…On the other hand, all values of g have the highest t w =ðrU 2 max Þ occurring around the distal orifice lip. This observation is similar to that of Steiger et al (1987) and of Lo¨w et al (1993) in their rigid or elastic lateral aneurysm models of g ¼ 0 . Suzuki and Ohara (1978) in their in vivo investigation pointed out that the blood flow often leads to the orifice wall reinforced by proliferation of intima.…”
Section: Wall Shear Stress and Pressuresupporting
confidence: 88%
“…A previous in vitro study demonstrated that there was no remarkable difference in flow characteristics between rigid and elastic aneurysm models. 34 Given the difficulty of accurate measurement of shearing velocity on a moving wall, reasonable flow simulation can be performed with rigid aneurysm models. This experimental model allows the comparison of the wall shear stress profile with the morphology, geometric disposition, location, and natural history of aneurysms.…”
Section: Geometrically Realistic Acrylic Aneurysm Modelmentioning
confidence: 99%
“…Ferguson 26 compared the elasticity of aneurysms to that of major intrancranial arteries and observed that aneurysms are relatively indistensible, indicating a loss of elastin within their walls. The in vitro experiments of Steiger et al 70 on lateral, saccular aneurysms demonstrated that the flow within an aneurysm is much more sensitive to the pulsatile nature of the cardiac waveform than to the effects of vessel wall deformation. Additionally, others 23,60,83 showed that although wall elasticity slightly decreases the magnitude of the wall shear stress, the overall flow and stress patterns within the vessel remain unchanged.…”
Section: Computational Setupmentioning
confidence: 98%